Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acsmacrolett.6b00243
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Approach toward Robust, Sustainable, Multiple-Shape-Memory Materials

Abstract: We report biomass-derived, shape-memory materials prepared via simple reactions, including "grafting from" ATRP and TAD click chemistry. Although the biomass, including plant oils and cellulose nanocrystals, has heterogeneous chemical structures in nature, these materials exhibit excellent multiple shape-memory properties toward temperature, water, and organic solvents, which are comparable to petroleum counterparts. The work presented herein provides burgeoning opportunities to design the next-generation, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…prepared a novel SMPs with two types of crosslinked structure (covalently crosslinked and physically crosslinked by the hydrogen bonds) using biomass resources that involves plant oils and cellulose nanocrystals. And the research shows that those SMPs have multiple responsive and multi‐shape memory properties . This work opens a new avenue to design the next‐generation SMPs by utilizing biomass resources.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…prepared a novel SMPs with two types of crosslinked structure (covalently crosslinked and physically crosslinked by the hydrogen bonds) using biomass resources that involves plant oils and cellulose nanocrystals. And the research shows that those SMPs have multiple responsive and multi‐shape memory properties . This work opens a new avenue to design the next‐generation SMPs by utilizing biomass resources.…”
Section: Introductionmentioning
confidence: 78%
“…The reason of this result could be explained by that EC‐ g ‐(PLMA‐ b ‐P(LMA‐ co ‐THFMA700)) with semi‐block architecture was capable of micro‐phase separation which leading to two thermal transition to fix two distinct shapes. However, EC‐ g ‐P(LMA‐ co ‐THFMA700) with random architecture was homogeneous which only have one thermal transition to achieved dual‐shape memory …”
Section: Resultsmentioning
confidence: 99%
“…In our recent studies, thermoplastic polymers with pendant fatty chains, originally from soybean oil, were designed and synthesized . Compared with triglycerides from soybean oil, these soy‐based polymers contain tens to hundreds of unsaturated fatty groups in each polymer chain, depending on molecular weight of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous polymer systems making use of a highly efficient click reaction, namely, the coupling of 1,2,4‐triazoline‐3,5‐dione (TAD) with double bonds according to DA or Alder–ene (AE) pathways, have been reported . In contrast to furan/maleimide DA reaction, this coupling reaction proceeds extremely fast at room temperature without the addition of any catalyst, leading to the formation of irreversible adducts in most cases . In addition, Baran et al reported a thermally reversible protection strategy of indole moieties by TAD via AE reaction at 0 °C .…”
Section: Introductionmentioning
confidence: 99%